Analisis Kemampuan Problem Solving dalam Penerapan Bidang Fisika Terapan Kemaritiman Sub Materi Vektor pada Siswa/i di SMA Negeri 1 Sukorejo - Lusiani Lusiani; Andi Hendrawan; Supriyanto Supriyanto (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The purpose of the following study is to describe the Problem Solving ability in the Application of Maritime Applied Physics Sub-Vector Material to Students at SMA Negeri 1 Sukorejo, this is studied because the description obtained can later be relevant to the use of learning methods and media used as steps to improve student learning outcomes. . The method used is observation and literature review . In this study the authors took the location in SMA Negeri 1 Sukorejo. Sampling used a random sampling technique in the Mathematics and Natural Sciences class which received vector material. Learning outcomes in the cognitive domain are obtained by using an instrument in the form of a Student Worksheet. It was obtained that the overall average ability of students to use problem solving steps was 99.12, meaning that it was more than 70% and this could be categorized as very capable or having very good abilities. The conclusion in this study is the analysis of Problem Solving Ability in the Application of Maritime Applied Physics, Sub Vector Material for Students at SMA Negeri 1 Sukorejo. Overall, the average ability of students to use problem solving steps is 99.12, which means more than 70% and this is can be categorized as very capable or have very good abilities.